Migration, ethnicity and economic integration - Amelie F. Constant; Klaus F. Zimmermann (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
This chapter deals with the economic and ethnic diversity caused by international labor migration, and their economic integration possibilities. It brings together three strands of literature dealing with the neoclassical economic assimilation, ethnic identities and attitudes towards immigrants and the natives, and provides an analysis in understanding their interactions. The issue of how immigrants fare in the host country especially in terms of their labor force participation and remuneration has been the core of research in the labor migration literature. If immigrants fare as well as the natives, then they are economically assimilated. While some immigrant groups do, most do not, especially in Europe. Of equal importance is how immigrants identify with the culture of their home and receiving countries, and if natives and immigrants have the right attitudes about each other. Ethnic identities and attitudes seem to be less affected by the economic environment but have implications for economic performance.
Keywords: F22; J15; J16; Z10; 330; Ethnicity; ethnic identity; acculturation; migrant assimilation; migrant integration; work; cultural economics; Migranten; Ethnische Beziehungen; Berufliche Integration; Soziale Integration; Ethnopsychologie